Faktor Komorbid Yang Mempengaruhi Kejadian Kematian Pasien Covid-19 Di Rumah Sakit - Rajagukguk, Marlina (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Covid-19 is a pandemic outbreak determined by WHO. WHO recorded more than 118 thousand cases of infection in 114 countries, 4,291 died while others were hospitalized. The existence of comorbidities is one of the causes of death because comorbids increase the severity. The number of confirmed cases of Covid-19 in 2021 in the Medan city area was 15,872 people and 475 people died. The purpose of this study was to determine the prevalence of confirmed Covid-19 patients who died in hospital based on the presence of comorbidities. This research is a type of analytical research with a quantitative approach. The research design used was cross-sectional. Sampling used a secondary sample in the form of medical records of confirmed Covid-19 patients with comorbidities who died and lived and then processed using SPSS with the chi square test. Based on research conducted, the sex of the most confirmed Covid-19 case respondents was male (61%) than female (39%). Based on the degree of severity, severe severity (54%), and moderate (46%). Cases who died with the majority age of 46-65 years were 28 people (57%). Cases died with 1 comorbid 29 people; the majority of HT 18 people (62%), with 2 comorbid 19 people; the majority of HT and DM were 16 people (84.2%), and 3 comorbidities namely HT, DM and heart disease were 2 people (1%). Statistical test results with three variables, namely age, number of comorbidities and types of comorbidities. Variables with p = <0.001 were the type of comorbidity and the number of comorbidities. Age with a p value = 0.048 means that there is an influence of age on the incidence of death. Cases with a single morbidity were more common and the mortality rate was higher than ≥ 2 comorbidities.